Accidental wetlands - A southern African case study from the Kgaswane Mountain Reserve, Rustenburg. Issue 4 (5th October 2021) - Grundling, R.E.; Turner, D.P.; Grundling, P.; Beckedahl, H.; Haussmann, N.S.
ABSTRACT: Wetlands form part of a diverse range of habitats and play an important role in the ecology and hydrological cycle but are amongst the most threatened ecological systems. It is therefore critical to understand the hydrology of wetlands, and their contributing water sources in particular, to ensure appropriate management of these systems. Land use activities not only alter the runoff characteristics of catchments, but also often result in modified flow regimes in watercourses. Wetlands often develop accidentally in anthropogenic landscapes and are not uncommon. However, these wetlands are poorly documented and researched. An accidental wetland formed in the Kgaswane Mountain Reserve, Rustenburg, due to leaking water infrastructure. The aim of this project was to categorise the wetland and confirm its origin, focussing on the role of the leakage. Methods included hydrogeomorphic classification, water ion composition analysis, as well as infield temperature and electrical conductivity measurements. Historical satellite imagery was used to study the evolution of the wetland over time. The electrical conductivity and ionic composition results suggest an unnatural water source, providing support that a leaking pipe caused the wetland to form. Management of accidental wetlands is discussed and the potential for future, related research is contemplated.